Marketing knowledge management, innovation process, learning capability, environmental dynamism and Nigerian SMEs marketing innovation performance - Muddaha, Garba; Yeoh, Khar Kheng; Sulaiman, Yaty (2017)
Marketing innovation is crucial to the success of Small and Medium Enterprises SMEs.As SMEs are faced with the challenge of globalization, it is the duty of managers to mobilize internal and external resources, and as well develop resources deployment capabilities.Equally, it is the duty of managers to introduce new marketing strategies that will improve the overall marketing performance. Hence, marketing innovation is critical to SMEs` survival, while, lack of it may hamper their growth. Therefore, in line with Resource-Based View (RBV) and Dynamic Capability View (DCV), the study proposes that marketing knowledge management, innovation process and learning capability will promote marketing innovation performance of Nigerian SMEs.A framework that investigates the moderating effect of environmental dynamism on the relationship between marketing knowledge management, innovation process, learning capability and marketing innovation performance is developed. Based on the research framework, the study contributed to literature. In addition to theoretical contribution, the study also has some practical implications.First, the study will educate managers of SMEs on their roles in terms of resources mobilization and resources deployment capabilities.Second, the study will assist greatly in the re invigoration of Nigerian SMEs, particularly in the pursuit of marketing innovation performance and realization of corporate goals. Third, the study will help managers to focus towards reversing the trend of premature death of SMEs in Nigeria.